Persistent Mullerian Duct Syndrome: A Rare But Important Etiology of Inguinal Hernia and Cryptorchidism - BEREKET, ABDULLAH; CANMEMİŞ, ARZU; KARADENİZ CERİT, KIVILCIM; DEMİRCİOĞLU, SERAP; KIRKGÖZ, TARIK; GÜRAN, TÜLAY (KARGER, 2020)
Homozygous loss of function mutations in genes encoding anti-Mullerian hormone (AMH) or its receptor (AMHRII) lead to persistent Mullerian duct syndrome (PMDS). PMDS is characterized by the presence of a uterus, fallopian tubes, cervix, and upper vagina in fully virilised 46,XY males. Both surgical management and long-term follow-up of these patients are challenging. Four cases with PMDS presented with cryptorchidism and inguinal hernia, and laparoscopic inguinal exploration revealed Mullerian remnants. Three of the patients had homozygous mutations in the AMH gene, one with a novel c.1673G>A (p.Gly558Asp) mutation, and one patient had an AMHRII mutation. All patients underwent a single-stage laparotomy in which the fundus of the uterus was split along the midline to release testes and to avoid damaging the vas deferens or the deferential artery. Biopsy of Mullerian remnants did not reveal any malignancy. The cases presented here expand the clinical and molecular presentation of PMDS. Cryptorchidism and inguinal hernia in the presence of Mullerian structures in an appropriately virilised 46,XY individual should suggest PMDS. Long-term reproductive and endocrinological surveillance is necessary.
Keywords: AMH; AMHRII; Cryptorchidism; Inguinal hernia; Persistent Mü llerian duct; GENE; MUTATIONS; PATIENT; AMH